The study of association between candidate gene polymorphisms and age-dependent diseases in population from Kazakhstan (International Journal of Biology and Chemistry, 2014)
Here, we show that several aging related genes may serve as the genetic risk factors for cervical, esophagus and colorectal cancers. We examined the genes involved in the processes of xenobiotics detoxification (GSTM1 and GSTT1), DNA repair (XRCC1, XRCC3, hMLH1), cell cycle regulation andapoptosis (CCND1, TP53, DCC). The study results will lead to development of screening for detection of individuals susceptible to esophageal, cervical and colorectal cancers. Introduction of the screening programs will allow the early and effective preventive measures that will reduce cancer incidence and mortality in Kazakhstan.